Language Style of Qus bin Sa'idah's Khutbah Without Arabic Rhymes; Arabic Stylistics Study - Taufiq, Mirwan Akhmad; Mush Firoh, Dewi Maisyatun (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
Sermons (khutbah) were popular media to influence the public during the Jahiliyah era; even today, speeches or orations are still the choices for conveying general ideas in a society that has relied heavily on written media. This study aims to reveal the selected phonological form, the word choice, and the arrangement of sentences written in the text of Qus bin Saidah’s speech. This research method uses descriptive qualitative. The primary source is the text of Qus bin Saidah’s speech. The data collection technique uses the sima technique by examining the speech text repeatedly and in detail. Data analysis techniques were carried out by collecting, reducing, and interpreting data. The finding of this research is the selection of light letters to be expressed behind the dense and heavy content of meaning. Notes with a soft intonation are sometimes believed to convey a message to listeners, even with a severe and rich statement. The choice of words is also appropriate for influencing the public to listen to Qus bin Saidah’s ideas. Likewise, the varied and exciting sentence structure models also make the listeners persist in listening and do puzzles about what beautiful arrangements will be conveyed in the sermon.